2020
DOI: 10.1186/s12879-020-4855-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes mellitus on short-term prognosis of 227 pyogenic liver abscess patients after hospitalization

Abstract: Background: Pyogenic liver abscess (PLA) is an inflammatory disease with increasing incidence. When it occurs with diabetes mellitus (DM), the risk of recurrence and mortality may increase. However, the effect of DM on the short-term prognosis of PLA patients after hospitalization remained unknown. Methods: Two hundred twenty-seven PLA patients who received treatment at the First were retrospectively enrolled. They were divided into two groups as the DM group (n = 61) and the Non-DM group (n = 166). In the DM … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The mortality rate in the early 1900s was 60–80%; however, recent studies have reported a mortality rate of 2–13% [ 31 ]. According to previous studies, comorbid diseases and risk factors such as underlying DM, malignancy, or liver cirrhosis have been associated with poor prognosis [ 7 , 32 ]. In the present study, in-hospital mortality was as low as 2%, and upon reviewing the cause of death, most patients died of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate in the early 1900s was 60–80%; however, recent studies have reported a mortality rate of 2–13% [ 31 ]. According to previous studies, comorbid diseases and risk factors such as underlying DM, malignancy, or liver cirrhosis have been associated with poor prognosis [ 7 , 32 ]. In the present study, in-hospital mortality was as low as 2%, and upon reviewing the cause of death, most patients died of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Comorbidities such as hypertension, diabetes mellitus, cardiovascular and respiratory diseases are often associated with poor outcomes in critically ill patients. 5 , 6 Due to improvement in the management of these conditions, however, several recent studies have indicated that serious comorbidities are not independent risk factors for mortality in the ICU. 7 , 8 The elderly patients are expected to consume more ICU resources in the future.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive search of the PUBMED from 1966 for “liver abscess/hepatic abscess and” AND “ Pseudodomonas maltophilia / Xanthomonas maltophilia / Stenotrophomonas maltophilia”, revealed very few number of such cases [ [6] , [7] , [8] , [9] , [10] , [11] ]. Of these, three cases were in immunocompromised patients comprising of diabetes, human immunodeficiency virus (HIV) infected, and a neonate each [ [6] , [7] , [8] ], while, two cases occurred in apparently immune-competent persons [ 9 , 10 ]. One case was described as a part of microbiological profile of pyogenic liver abscesses in patients <70 years age [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both aerobes and facultative anaerobes like Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter spp, Staphylococcus spp , Enterococcus spp , Citrobacter spp , Streptococcus spp as well as obligate anaerobes like Bacillus fragilis , Bacteroides species, Fusobacterium , and Clostridia have been implicated [ [2] , [3] , [4] , [5] ]. Stenotrophomonas maltophilia, an environmental Gram-negative bacterium with low virulence, heralded widely as an emerging global opportunistic pathogen, has only rarely been isolated from PLA cases before [ [6] , [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%